Diseño, cálculo, selección de componentes, elaboración de planos de fabricación y manual de banco de pruebas para bombas y motores oleohidráulicos para la empresa Hydaulictech SAS, con capacidad de 55 kW y adquisición de señales de las variables de presión, caudal, torque y velocidad rotacional. (2020)
The target of this paper is design, calculation, and selection of hydraulic, mechanical, electrical and electronic components for manufacture and implementation of a hydraulic pumps and motors test bench, propriety of HYDRAULICTECH SAS, with power of 55 kW and pressure, flow, torque and rpm acquisition signals system. The hydraulic test bench will be used to diagnose the performance of hydraulic pumps and motors before and after repair process. The need of this equipment, is due to HYDRAULICTECH SAS customers requests. They have required status reports before and after parts repairs, demanding accurate diagnoses, through working conditions simulation tests. These conditions must be similar to the operation in the machines. The tests must be based on original equipment manufacturer criteria working. HYDRAULICTECH SAS has analyzed its focus market, the replaced and repaired parts reports. It has determined that the test bench capabilities to pressure and flow must be 300 bar, 152 L/min for hydraulic pumps, torque up to 450 Nm for hydraulic motors. The company requires that these variables data be acquired, displayed and stored during each test in the PARKER Service Master Plus Kit, for subsequent analysis and report preparation for the customer. The Company has destined for manufacturing of the test bench a 55 kW electric motor, a closed loop hydraulic pump with 118,7 cm3/revolution, and a hydraulic motor with 118,7 cm3/ revolution.